Persepsi Mahasiswa Pascasarjana PAI terhadap Sarana dan Prasarana Pendidikan: Ditinjau menggunakan Evaluasi Model CIPP - Riswandi R; Nurlathifah Thulfitrah B (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study was motivated by the importance of the availability and quality of infrastructure as a major supporting factor for the comfort and smooth running of the lecture process at the postgraduate level. The purpose of this study was to evaluate educational facilities and infrastructure based on the perceptions of postgraduate students in the Islamic Education Study Program (PAI) using the Context, Input, Process, and Product (CIPP) evaluation model. This research is an evaluative study with a qualitative approach, involving PAI graduate students as research subjects. Data collection was conducted through questionnaires, in-depth interviews, and field observations, then analyzed using the Question Discourse technique to obtain a comprehensive understanding of the students' experiences and assessments. The results show that students view facilities and infrastructure as important to very important in supporting the lecture process. In general, the facilities are considered adequate, but there are still limitations in the air conditioning system and internet network stability, which affect the comfort and effectiveness of learning. The implications of this study emphasize the need for continuous improvement in the quality, maintenance, and management of facilities and infrastructure to support the quality of PAI postgraduate education.